Biological Activity Study of Schiff Base ligands and their Complexes: A Review - Lekaa K. Abdul Karem (Journal of Global Pharma Technology, 2016)
Schiff  Bases (SB)  stand for  multipurpose  ligands  created  from  prime  amines  condensing  with carbonyl groups. These represent imperative compounds in pharmaceutical and medical domains as a consequence of their widespread spectra of organic performances. The majority of them exhibit antibacterial, antifungal and antitumor activities. Transition metal compounds based on biological SB ligands were extensively investigated. This study reviews the synthesizing and organic activities of SB and its complexes. Keywords: Metal complexes, Schiff Bases, Antitumor activity, Antimicrobial activity, Nonlinear optical properties.